PROSES METAKOGNITIF SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA MEMILIH OPERASI BILANGAN PECAHAN - ANARISA (Pusat Penelitian dan Pengembangan Reka Karya Amerta (REKARTA), 2019)
This research describes the student metacognition process of choice operation of fraction in problem solving. This research using qualitative approach. The subjects consisted of two students in VI class, they were in the lower and upper grade. Instruments in this research is question of mathematical problem solving test and interview guide. The result of this research is the lower and upper grade can understand the concept of fraction, choose the correct operation and show different description. Students still stuck to the concept taught before without knowing the true principle of fraction operation strategy.